Industrial Growth and the Quality of Institutions : What Do (Transition) Economies Have to Gain from the Rule of Law? - Grigorian, David A.; Martinez, Albert (World Bank, Washington, DC, 2014)
The authors empirically test the link between industrial growth and indicators of institutional quality. They find significant evidence that institutional quality affects inindustrial growth in 27 Asian and Latin American countries. Their results suggest that the development of the legal and regulatory framework works its way to industrial growth through both investment and total factor productivity. The implications for policymakers in transition economies: Institution building should complement privatization, public and private investment in education, research and development, and measures to promote foreign direct investment. Specifically, policymakers should try to reduce corruption, eliminate bureacratic barriers, and improve the legal environment and contract enforcement. Special attention should also be given to measures to deepen financial intermediation, improve the financial sector infrastructure, and increase the efficiency of financial transactions.